Anti-invasion effect of crebanine and O-methylbulbocapnine from stephania venosa via down-regulated matrix metalloproteinases and urokinase plasminogen activator - Yodkeeree S. (2014)
The alkaloids isolated from Stephania venosa (S. venosa) have been shown to inhibit the proliferation and to induce the apoptosis of cancer cells. However, the anti-metastatic effect of the alkaloids on cancer cell invasion is unknown. In this study, we investigated the anti-invasive properties of four alkaloids from S. venosa, crebanine (CN), O-methylbulbocapnine (OMBC), tetrahydropalmatine (THP), and N-methyltetrahydropalmatine (NMTHP), in HT1080 human fibrosacroma cells. Treatment of the cells with 15 μg/mL of CN and OMBC reduced the chemo-invasion of HT1080 cells to 45 and 50%, respectively, whereas THP and NMTHP had a negative effect. On the other hand, CN and OMBC had no effect on cell migration. Matrix metalloproteinases (MMPs) and urokinase plasminogen activator (uPA) are the extracellular matrix (ECM) degradation enzymes that play an important role in cancer cell metastasis. Results from zymography and western blot analysis showed that CN and OMBC comparatively reduced MMP-2, MMP-9, MT1-MMP and uPA expression in a dose-dependent manner. However, CN and OMBC had no effect on the activity of collagenase, MMP-2 and MMP-9. We also found that CN and OMBC reduced the nuclear translocation and DNA binding activity of nuclear factor kappa B (NF-κB), which is the expressed mediator of ECM degradation enzymes. These findings demonstrated that CN and OMBC mediated HT1080 cell invasion by the reduction of MMP-2, MMP-9, uPA and MT1-MMP expression, possibly by targeting of NF-κB signaling pathway in the HT1080 cells. © 2013 The Pharmaceutical Society of Japan.